Daily and seasonal human mobility modulates temperature exposure in European cities - Guo-Shiuan Lin; Maider Llaguno-Munitxa; Gabriele Manoli (PLoS ONE, 2025)
Extreme temperatures pose a serious threat to human health, especially in urban areas where the majority of the world population is living. Temperature-related risks are exacerbated by urban-induced warming but existing exposure assessments rely on a static residential population, thus overlooking space-time changes in population density and their covariation with urban temperatures. Here we combine 1-km monthly daytime and nighttime population estimates for 80 European cities with existing high-resolution urban climate simulations to quantify the impact of daily and seasonal mobility on residents’ exposure to heat and cold. Using city-specific exposure-response curves and the respective minimum mortality temperatures as thresholds to define hazardous conditions we calculated that, on daily timescales, commuting towards city centers causes a 7.8% average increase (IQR:1.0-12.9%) in summer heat exposure but, during winter, it provides a slight protective effect against cold. On seasonal timescales, changes in total population are out of phase with the temperature cycle in most European cities, leading to a lower exposure to heat, with the exception of touristic destinations where exposure increases, on average, by 0.9% during the warmest months. These results highlight the key role of human mobility for heat risk assessment and adaptation and they reveal the existence of general exposure trends that hold across diverse cities and climates.